Effectiveness of Earthworm Extract on the Lipid Profile of Diabetic Wistar Rats - Suandy, Suandy; Chiuman, Linda; Halim, Angel Jonathane (Jurnal Kedokteran Brawijaya, 2024)
Various metabolic diseases, such as diabetes mellitus, are characterized by hyperglycemia, stemming from decreased insulin action, secretion, or both. The use of chemical medicines for diabetes mellitus, especially acarbose, involves regulating the digestion and absorption of complex carbohydrates. However, acarbose may disrupt liver function, prompting exploration into alternative sources for treatment, such as earthworm extract. The purpose of this study was to identify the effectiveness of ethanol extract and coelomic fluid from earthworms (E. eugeniae) on the lipid profile of male diabetic wistar rats (R. norvegicus) in vivo. The research hypothesis is that earthworm extracts could effectively lower the lipid profile of diabetic Wistar rats. This research is experimental research with pre-test and post-test control study group design, using an in vivo method. The results of the one-way ANOVA test of HDL were p=0.441; p=0.441; p=0.000; for LDL were p=0.691; p=0.101; p=0.049; for total cholesterol were p=0.107; p=0.347; p=0.486; and for triglycerides were p=0.028; p=0.926; p=0.553 on days 0, 7, and 14, respectively. Based on the research data, both ethanol extract and a combination of ethanol extract and coelomic fluid were able to reduce lipid profile levels on the 7th and 14th days. Earthworm extract has the potential to promote repair of β cells and is anti-inflammatory which can be used to reduce lipid profile levels.